KARAKTERISTIK EKSEKUTIF TERHADAP TAX AVOIDANCE DENGAN LEVERAGE SEBAGAI VARIABEL INTERVENING - Verani Carolina; Maria Natalia; Debbianita Debbianita (University of Merdeka Malang, 2014)
This research aimed to examine the influence of the executive characteristic on corporate tax avoidance. Risktakers executive tended to be more courageous and aggressive in taking decision related to the tax. On thecontrary, the risk averse executive tended to be carefully (Low, 2006). This research used leverage as interveningvariable. Therefore, there was an assumption that the executive characteristic determined the corporateleverage which then influenced their tax avoidance in the company. Manufacturing companies which werelisted in Indonesia Stock Exchange during the period 2010-2012 were used as samples. This research usedpurposive sampling method to select the sample with the criteria as follows: they were listed in Indonesia StockExchange during the period of 2010-2012, they made a profit during the period of 2010-2012, and they usedrupiah as reporting currency. Data was processed using path analysis and the result showed that the executivecharacteristic had an impact on corporate tax avoidance with leverage as the intervening variable. The resultof this research could be used for the investors to assess the corporate tax avoidance before they made a decision,and also for the policy makers to detect the corporate tax avoidance.